Evaluation of solvent effects on NMR metabolic profiling of Passiflora cincinnata Mast. Cv. BRS Sertão Forte. - SANTOS, R. F. dos (2024)
Passiflora cincinnata Mast. is a native species from the Caatinga biome (Brazil), commonly known as “maracujá-do-mato” and “maracujá-da-Caatinga”. P. cincinnata leaves were subjected to microextraction with 70% ethanol-water mixture as follows: 1.5 mL of the solvent mixture was added in 50 mg of powdered leaves and sonicated for 15 min. After solvent removal, the samples were analyzed by nuclear magnetic resonance (NMR). Besides signals from primary metabolites, the chemical profile revealed the presence of isovitexin, vitexin-2”-O-xyloside, and trigonelline. Tracking these compounds might be of interest to metabolomic studies.